2019
DOI: 10.3390/en12224247
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Water Generation on a Mediterranean Island in Greece

Abstract: Population growth, increasing droughts, and high irrigation needs are all factors that create freshwater shortage problems on islands. The pressing needs of remote islands usually call for water transport from the mainland or other neighboring islands, at a high cost. This study evaluates the design and economic viability of an alternative, sustainable water supply network on the Mediterranean island of Skyros in Greece. The proposed water supply system provides the island with potable water from desalination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…He also mentioned that the abundant solar and wind energy resources of Crete can be deployed for electricity generation over-meeting the annual power demand of the island. Fernandez-Gil et al, 2019 [33] have studied the sustainable water generation in the Greek island Skyros. The authors stated that population growth, increasing droughts and high irrigation needs create deficit in fresh water.…”
Section: Literature Surveymentioning
confidence: 99%
“…He also mentioned that the abundant solar and wind energy resources of Crete can be deployed for electricity generation over-meeting the annual power demand of the island. Fernandez-Gil et al, 2019 [33] have studied the sustainable water generation in the Greek island Skyros. The authors stated that population growth, increasing droughts and high irrigation needs create deficit in fresh water.…”
Section: Literature Surveymentioning
confidence: 99%
“…For energy saving, it is highly convenient to take advantage of the cogeneration concept, which is highly recommendable, since it can be carried out by use of waste heat from a standalone power plant, leading to the lowest desalination costs. Several examples of case studies have been proposed and analyzed in the past, such as [7] and [8]. The turbine exhaust gas was supplied to the heat exchanger, by which the feedwater temperature rose to about 70-90 • C. The obtained heated water passed through the evaporation chamber, in which the evaporation process took place.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have focus on the optimal combination of components. For example, Fernández-Gil and Petrakopoulou showed that implementing RE-desalination systems on Skyros Island, Greece yields freshwater at a cost of 2.75 USD/m 3 , which is 52% lower than imported freshwater [10]. Tafech et al show that reverse osmosis (RO) powered by a PV-wind system can yield freshwater at a cost of 1.87 USD/m 3 on King Island, Australia [11].…”
Section: Introductionmentioning
confidence: 99%
“…Note that excessive desalination turndown could arise, which will damage the desalination plant [16]. • Case study in off-grid areas in Iraq • Solar-wind-diesel-RO system has lowest water generation costs [11] • Case study based on King Island, Australia • Solar PV-RO has the lowest water generation cost • Water storage important for dealing with uncertainties [18] • Case study in Algarve, Portugal • Decentralized system yields lowest generation cost [19] • Economic feasibility of supplying water demand of US coastline via RO • US electricity consumption will increase by only 0.5% [10] • Case study in Skyros, Greece •…”
Section: Introductionmentioning
confidence: 99%